PEMANFAATAN SISTIM INFORMASI AKUNTANSI (SIA) DALAM MENINGKATKAN KINERJA PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN GORONTALO - Felmi D Lantowa; Fitri Melynsyah Yusuf (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2023)
The Accounting Information System (SIA) that will be provided with training and assistance in its use to BUMDes administrators throughout Gorontalo Regency, namely the accounting information system as stipulated in PP Number 11 of 2021 article 58 concerning BUMDes accountability. The short-term goal is to meet the needs of BUMDes management for a system or tool used in managing BUMDes finances in accordance with applicable accounting principles. The method approach used to implement the solution is the training and mentoring method, by carrying out four important stages, namely the preparation stage, the implementation stage, the monitoring and evaluation stage and the mentoring stage. The result of this activity was that the participants' response to this activity was very good. This can be seen from the enthusiasm of the participants in the question and answer session both on material about financial health in managing BUMDes finances and on material for recording financial reports using SIA. The participants' questions were motivated by the financial condition of the business they manage and the commitment to carry out financial management in a better direction go out